PENGARUH PARTISIPASI PEMAKAI DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP KESUKSESAN PENGEMBANGAN SISTEM INFORMASI AKUNTANSI SERTA DAMPAKNYA TERHADAP PROSES PENGAMBILAN KEPUTUSAN - Nasrizal, Nasrizal (Program Studi Akuntansi FPEB UPI, 2013)
The objective of this research was to examine empirically the influence of user participation and top management support on success of accounting information system development and its impact on decision making process. The analysis units were the hospital in Pekanbaru city. The election of sample is by using technique of probability sampling with method of simple random sampling. The statistical method used to test the hypothesises was path analysisÂ with AMOS 20 Â program. The result shows that only the first hypothesis did not have a significant influence, while the others hadÂ a significant influence.